Phytochemical Profiling and Antioxidant Assessment of Indian Cymbalaria Muralis Extracts: Phytochemical Profiling and Antioxidant Assessment of Indian Cymbalaria muralis Extracts - Beniwal, Ankita; Chaudhary, Jasmine; Jain, Akash (Scripta Medica, 2026)
Background/aim: Cymbalaria muralis (ivy-leaved toadflax) is a small creeping plant native to Europe, South Africa and some regions of India. Indian Cymbalaria muralis is recognised as a plant of traditional importance, but scientific literature available for its pharmacological activities as well as its bioactive constituents is very limited, hence this plant draws more attention for research. Aim of this study was to access phytochemical profile and potential antioxidative potential. Methods: Phytochemical profiling of Indian Cymbalaria muralis methanolic (CMME) and aqueous extract (CMAE) was carried using gas chromatography-mass spectrometry (GC-MS) and liquid chromatography–tandem mass spectrometry (LC-MS/MS) techniques and LC-MS/MS techniques. In addition to determining total phenolic content (TPC) and total flavonoid content (TFC), antioxidant activity of both extracts was evaluated using DPPH radical scavenging method. Results: The GC-MS spectrum of CMME and CMAE showed a presence of 52 compounds (86 peaks) and 8 compounds (11 peaks) respectively with majority of compounds corresponding to fatty acids or lipids. LC-MS/MS studies further confirmed the presence of some anticipated compounds, namely apigenin, luteolin, chrysoeriol 7-glucosides, 7-glucuronides, apigenin 7-O-glucoside, chrysoeriol 7-rutinosides, diosmin, catapol, linarin, glucosyringic, 8-epimuraloside and 8-epiloganic acid with discovery of 3 novel metabolites namely harpagide, aucubin and actinidine. The total phenolic content (TPC) was found to be 91.33 ± 0.67 mg/g (CMME) and 68.75 ± 0.65 mg/g (CMAE), total flavonoid content (TFC) in CMME and CMMA was 30.16 ± 0.15 mg/g and 10.04 ± 0.17 mg/g respectively. In DPPH radical scavenging activity, CMME was found as better antioxidant (IC50-40.82 g/mL) in comparison to CMAE (IC50-75.20 g/mL). Conclusion: The Indian Cymbalaria muralis exhibited remarkable antioxidant activity and rich phytochemical profile.